Indonesia’s Delimited Maritime Boundaries - Forbes, Vivian Louis. author. aut Link
XVII, 266 p. 38 illus., 19 illus. in color.
Keywords: This book examines the delimited maritime boundaries of Indonesia with its neighbours. It features carefully drawn maps based on the geographical coordinates of the defined maritime boundaries; the reproduction of a complete set of the primary documents with direct relation to the boundaries; and a comprehensive narrative on the geography and the historical development of the archipelagic State. Indonesia has an immense maritime domain that encompasses much of the sea between Australia and the Asian mainland. In addition, Indonesia is itself made up largely of water: in excess of 17,000 islands, Indonesia’s archipelagic and territorial waters together form about three-fifths of the country’s sovereign territory. This book offers readers clear, accessible information on the maritime boundaries of the world’s largest archipelagic state.